Mesoangioblast delivery of miniagrin ameliorates murine model of merosin-deficient congenital muscular dystrophy type 1A - Domi, Teuta (Skelet Muscle, 2015)
BACKGROUND: Merosin-deficient congenital muscular dystrophy type-1A (MDC1A) is characterized by progressive muscular dystrophy and dysmyelinating neuropathy caused by mutations of the α2 chain of laminin-211, the predominant laminin isoform of muscles and nerves. MDC1A has no available treatment so far, although preclinical studies showed amelioration of the disease by the overexpression of miniagrin (MAG). MAG reconnects orphan laminin-211 receptors to other laminin isoforms available in the extracellular matrix of MDC1A mice. METHODS: Mesoangioblasts (MABs) are vessel-associated progenitors that can form the skeletal muscle and have been shown to restore defective protein levels and motor skills in animal models of muscular dystrophies. As gene therapy in humans still presents challenging technical issues and limitations, we engineered MABs to overexpress MAG to treat MDC1A mouse models, thus combining cell to gene therapy. RESULTS: MABs synthesize and secrete only negligible amount of laminin-211 either in vitro or in vivo. MABs engineered to deliver MAG and injected in muscles of MDC1A mice showed amelioration of muscle histology, increased expression of laminin receptors in muscle, and attenuated deterioration of motor performances. MABs did not enter the peripheral nerves, thus did not affect the associated peripheral neuropathy. CONCLUSIONS: Our study demonstrates the potential efficacy of combining cell with gene therapy to treat MDC1A. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13395-015-0055-5) contains supplementary material, which is available to authorized users.